Mozart's The marriage of Figaro - Da Ponte, Lorenzo, 1749-1838 (Opera classics library., 2005)
A comprehensive guide to Mozart's THE MARRIAGE OF FIGARO, featuring Principal Characters in the opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, a complete, newly translated LIBRETTO with Italian/English side-by-side, selected Discography and Videography, Dictionary of Opera and Musical Terms, and an insightful and in depth Commentary and Analysis by Burton D. Fisher, noted opera author and lecturer.